Tips for Junior Doctors and Medical Students: Writing and Publishing Undergraduate Textbooks - Aliso Bradley; Katrina A. Mason; Mark A. Rodrigues; Ceen-Ming Tang; Matthew Wood; Katherine Lattey; Patrick Byrne; Michael Ross; Simon Maxwell; Zeshan U. Qureshi (University Library System, University of Pittsburgh, 2015)
NA